Physiotherapy students at school: The challenges and potentialities of a collaborative action with elementary school children - Marques, Rosana Niederauer; Ludke, Everton; Betat, Andressa; Quirino, Cássio da Silva (Seven Editora, 2024)
This article aimed to discuss the perceptions of students about training activities in the Physical Therapy course, as well as to analyze their ability to propose school activities that improve children's performance. The participants are 15 students of the Physical Therapy course at the Federal University of Santa Maria (UFSM) who, during the second semester of 2016, attended the discipline called Physical Therapy in Child Health, which aims to propose psychomotor activities that improve the performance of students. The practical work was developed in two Municipal Elementary Schools, with 19 children who attended these schools, located in the municipality of São João do Polêsine, central region of Rio Grande do Sul. The methodology of the work has a qualitative character, where the analysis is based on the principles of the narrative interview of Richardson (2011); Clandinin and Connely (2011); Jovchelovitch and Bauer (2004); Josso (2004). It was concluded that, in the perception of the students, the work developed is relevant in the professional training of physical therapists, mainly because they observed that it has generated positive impacts in the school community as well as in the academic community. DOI:https://doi.org/10.56238/sevened2024.009-001